Patient perceptions of the mandibular three‐implant overdenture: a practice‐based study. Issue 6 (19th February 2014) - Emami, Elham; de Souza, Raphael F.; Bernier, Jacques; Rompré, Pierre; Feine, Jocelyne S.
Abstract: Objectives: Although three‐implant overdentures have often been used in clinical practice, there are few studies to support this approach. Therefore, this study aimed to determine the magnitude of change in ratings of oral health‐related quality of life and to assess patients' satisfaction ratings with mandibular three‐implant overdentures. Materials and methods: This quasi‐experimental study examined oral health‐related quality of life and satisfaction with prosthesis in 135 edentate participants (mean age 61.6 ± 7.9 years) who received mandibular three‐implant overdentures from 2006 to 2009 in a private practice in Quebec, Canada. Data were collected from individual's dental records and a follow‐up survey. The Oral Health Impact Profile (OHIP‐20) was used to assess oral health‐related quality of life at baseline and at follow‐up. Satisfaction with the mandibular prostheses and perception of rocking movements were measured by use of a denture satisfaction questionnaire at follow‐up. Descriptive statistics, bivariate and multivariate statistical analyses were used to analyse the data. Results: Individuals who received mandibular three‐implant overdentures had statistically significant improvements in all seven domains of the OHIP‐20 from pre‐ to post‐treatment (total OHIP change score −25.1 P < 0.001). Pre‐treatment OHIP scores and rotational movement explained 58% of the variance in the OHIP's change score ( P ≤ 0.05). More than three quarters of the sample population (75.6%) were completely satisfied with their three‐implant overdentures, and 81.5% reported having no rocking movement. General satisfaction with the prostheses was not influenced by gender, type of fixture, or type of attachment. Conclusions: The treatment of edentulism by three‐implant overdentures has favourable patient‐based outcomes, with negligible perceptions of rotational movement. However, further research is needed to compare the efficacy of this alternative to other treatment modalities, such as the two‐implant overdenture.